Effect of obesity, dyslipidemia, and diabetes on trastuzumab-related cardiotoxicity in breast cancer - Kosalka, P. (Curr Oncol, 2019)
BACKGROUND: Clinical trials have demonstrated an increased risk of cardiotoxicity in patients with breast cancer (bca) receiving trastuzumab-based therapy. Diabetes, dyslipidemia, and obesity are known risk factors for cardiovascular disease. Studies have yielded conflicting results about whether those factors increase the risk of cardiotoxicity in patients with bca receiving trastuzumab. METHODS: In this retrospective cohort study, data were collected for 243 patients with bca positive for her2 (the human epidermal growth factor receptor 2) who were receiving trastuzumab and who were referred to The Ottawa Hospital Cardio-oncology Referral Clinic between 2008 and 2013. The data collected included patient demographics, reason for referral, cardiac function, chemotherapy regimen (including anthracycline use), and 3 comorbidities (diabetes, dyslipidemia, obesity). Rates of symptomatic cancer treatment–related cardiac dysfunction (sctcd) and asymptomatic decline in left ventricular ejection fraction (adlvef) were calculated for patients with and without the comorbidities of interest. RESULTS: Of the 243 identified patients, 104 had either diabetes, dyslipidemia, or obesity. In that population, the most likely reason for referral to the cardio-oncology clinic was adlvef. The combination of 2 or 3 comorbidities significantly increased the incidence of sctcd in our population, reaching a rate of 67% for patients with obesity and dyslipidemia [relative risk (rr): 2.2; p = 0.04], 69% for patients with obesity and diabetes (rr: 2.3; p = 0.02), and 72% for patients with all 3 risk factors (rr: 2.4; p = 0.08). CONCLUSIONS: The combination of 2 or 3 comorbidities significantly increases the incidence of symptomatic cancer treatment–related cardiotoxicity. Patients with bca experiencing cancer treatment–related cardiotoxicity who have a history of diabetes, dyslipidemia, and obesity might require more proactive strategies for prevention, detection, and treatment of cardiotoxicity while receiving trastuzumab-based treatment.